(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2020)
To estimate vulnerability of existing and newly designed buildings, we need to know their natural periods. Knowing the location of the building and its fundamental (longest) natural period, based on spectral seismic maps, we can estimate the level of its damage due to seismic event. Moreover, using impulse response method, we can separate fixed-base frequency, f1 from system frequency, fs. With this research we will try to define which parameters are needed for creating empirical equations for estimation of fundamental periods of existing and newly designed buildings in North Macedonia. We expect that the new proposed equations, compared with existing ones, will give better estimate of fundamental system periods Ts and fundamental fixed-base periods T1 for buildings in our country. In correlation with future seismic microzoning of big cities with Uniform Hazard Spectrum (UHS) method, this research will be excellent base for estimation of vulnerability and economic loss due to earthquakes.